Informality as an Important Feature of Luanda’s Urban Process. A Closer Look at Bairro Prenda - Venâncio, Joana (2015)
Observing Luanda, one usually distinguishes formal areas from informal settlements, the musseques. To understand its urban process, however, it is necessary to see beyond this dichotomy. Without any previous city plan, Luanda grew in a spontaneous way, mostly due to micro-scale social and economic dynamics. The attempts to formalize some areas usually resulted in social and economic segregation, as poor people from informal areas near the centre are expropriated and pushed towards the periphery. Our focus is on Bairro Prenda, as a closer approach to the city’s urban process. Evolving from farmland to musseque, later to a modernist neighbourhood and from then to now: a melting pot of formal and informal processes, in which informality illustrates how the city survived forty years of war (colonial 1961-1974; civil 1975-2002). It is the aim of this paper to question whether this urban informality should be fought or, on the contrary, is an integrating part of Luanda’s character and, as such, should be taken into account in its relationship with the world.